Relation between level of knowledge and waste management of biosanitary, and pollution generated in two university dental clinics - Chein Villacampa, Sylvia (2012)
The purpose was to relate the level of knowledge, biocontaminated waste management. and the level of pollution generated in two Dental Clinics: Clinicof the Faculty of Dentistry at the National University of San Marcos (San Marcos) and the Universidad Nacional Federico Villarreal (UNFV). The type of study was cross-sectional l. Attended by 299 people including students, teachers and maintenance staff. Was used an observation sheet and microbiological analysis. There was a low and very low level of staff knowledge about biocontaminated Waste Management. There were no gender differences in UNMSM staff (p = 0.55), while in UNFV, males showed less knowledge (p = 0.038). The biocontaminated and pathologic waste management from generation to final disposal is inadequate (UNMSM 92.3 % and 58.5 %, 100.0 % and 51.8 %UNFV respectively). The handling of needles is adequate (77.4 % UNMSM, UNFV 100 %). Were found mesophilic bacteria, heterotrophic bacteria and fungi within environments. In two spittoons were found Lactose + and Pseudomonas colonies. The level of knowledge was associated with improper management of contaminated biological waste, while was not related to the handling of sharps waste. It was concluded that exists relation between level of staff knowledge and inadequate management of biological and pathological waste. There is biological contamination in the studied environments clinics and lack of compliance with the technical standards of the Ministry of Health, with exception of needles waste.